Spreading Analysis of an SEIR Epidemic Model with Distributed Delay on Scale-Free Network (Journal of Nonlinear Modeling and Analysis, 2025)
A novel epidemic SEIR model with distributed delay on scale-freenetwork is proposed in this paper. The formula of the basic reproductionnumber $R_0$ for the model is given, and globally dynamic behaviours of themodel are discussed. Numerical simulations are carried out to demonstratethe main results.